Relating folksonomies with Dublin Core. (1st October 2010) - Catarino, Maria Elisabete; Baptista, Ana Alice
This article presents a research carried out to continue the project Kinds of Tags, which intends to identify elements required for metadata originating from folksonomies. It will provide information that may be used by intelligent applications to assign tags to metadata elements. Despite the unquestionably high value of DC and DC Terms, the pilot study revealed a significant number of tags for which no corresponding properties yet existed. A need for new properties was determined. This article presents the problem, motivation and methodology of the underlying research. It further presents and discusses the findings from the pilot study.